2016
DOI: 10.1259/bjr.20150773
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of epicardial adipose tissue in coronary calcium score and CT coronary angiography image data sets: comparison of attenuation values, thickness and volumes

Abstract: EAT may be measured by processing either the CS or CTCA image data sets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 37 publications
(81 reference statements)
2
20
0
1
Order By: Relevance
“…To further back these notions, epicardial adipose tissue density appears to increase on contrast-enhanced scans compared to unenhanced scans, favoring the hypothesis that it may present with a more developed vascularization to support its metabolic activity. This result is in line with findings from one study by La Grutta et al [ 12 ], who observed that epicardial adipose tissue density was significantly higher on contrast-enhanced CT scans. However, these authors reported density values lower than ours on unenhanced scans and higher values on contrast-enhanced scans, such differences being possibly due to different methods of epicardial adipose tissue segmentation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To further back these notions, epicardial adipose tissue density appears to increase on contrast-enhanced scans compared to unenhanced scans, favoring the hypothesis that it may present with a more developed vascularization to support its metabolic activity. This result is in line with findings from one study by La Grutta et al [ 12 ], who observed that epicardial adipose tissue density was significantly higher on contrast-enhanced CT scans. However, these authors reported density values lower than ours on unenhanced scans and higher values on contrast-enhanced scans, such differences being possibly due to different methods of epicardial adipose tissue segmentation.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, even though the association between an increased epicardial adipose tissue density and myocardial ischemia is still a matter for debate, analyzing the potential relation between its density and CAD may unravel the potential of the former as a cardiovascular risk biomarker [ 11 ]. In this regard, different studies have been conducted both with and without the intravenous administration of iodinated contrast agents [ 12 ]. As a consequence, the relationship between epicardial adipose tissue density and contrast enhancement may benefit from additional insights.…”
Section: Introductionmentioning
confidence: 99%
“…Larger, less dense, and poorly vascularized adipocytes may experience more oxidative stress leading to metabolic dysfunction and production of pro-inflammatory adipocytokines 19 . Importantly, however, there may be significant regional variation of adipose tissue characteristics, particularly within the pericardium 20 , and this may be reflected in regional variation of radiodensity 21 . Future studies in the HIV+ and general populations should consider more granular characterization of PCF volumes and radiodensity by location within the pericardium.…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial adipose tissue can be measured with different imaging techniques: ultrasonography (US), computed tomography (CT), and magnetic resonance imaging (MRI) (12,13). Cardiac CT angiography (CCTA) with volumetric acquisition shows the highest spatial resolution and reproducibility for quantitative analysis of EFV, including the assessment of the CT attenuation coefficient (14)(15)(16). A number of studies described EFV features mainly in asymptomatic subjects, with a minor proportion of symptomatic subjects.…”
mentioning
confidence: 99%